Immunometabolic bases of type 2 diabetes in the severity of COVID-19 - Viurcos-Sanabria, Rebeca (World J Diabetes, 2021)
The outbreak of coronavirus disease 2019 (COVID-19) is caused by the novel severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). COVID-19 and type 2 diabetes (T2D) have now merged into an ongoing global syndemic that is threatening the lives of millions of people around the globe. For this reason, there is a deep need to understand the immunometabolic bases of the main etiological factors of T2D that affect the severity of COVID-19. Here, we discuss how hyperglycemia contributes to the cytokine storm commonly associated with COVID-19 by stimulating monocytes and macrophages to produce interleukin IL-1β, IL-6, and TNF-α in the airway epithelium. The main mechanisms through which hyperglycemia promotes reactive oxygen species release, inhibition of T cell activation, and neutrophil extracellular traps in the lungs of patients with severe SARS-CoV-2 infection are also studied. We further examine the molecular mechanisms by which proinflammatory cytokines induce insulin resistance, and their deleterious effects on pancreatic β-cell exhaustion in T2D patients critically ill with COVID-19. We address the effect of excess glucose on advanced glycation end product (AGE) formation and the role of AGEs in perpetuating pneumonia and acute respiratory distress syndrome. Finally, we discuss the contribution of preexisting endothelial dysfunction secondary to diabetes in the development of neutrophil trafficking, vascular leaking, and thrombotic events in patients with severe SARS-CoV-2 infection. As we outline here, T2D acts in synergy with SARS-CoV-2 infection to increase the progression, severity, and mortality of COVID-19. We think a better understanding of the T2D-related immunometabolic factors that contribute to exacerbate the severity of COVID-19 will improve our ability to identify patients with high mortality risk and prevent adverse outcomes.